INOVASI PRODUK ICE CREAM DAN STIK AMPAS TAHU DALAM PEMANFAATAN AMPAS TAHU SEBAGAI USAHA PENGEMBANGAN PRODUK UMKM USAHA TAHU MAJU MANDIRI DESA PAYA BUJOK TEUNGOH - Riezky Purnama Sari; Nabilla, Ulya; Fajri, Rahmatul; Amelia; Nurviana; Muliani, Fitra; Fairus (Fakultas Teknik, Universitas Samudra, 2024)
Tofu production in Langsa City is mostly produced by small businesses, one of which is the UMKM Usaha Tahu Maju Mandiri. Based on initial observations, the problems faced by these MSMEs are not maximizing the use of solid tofu dregs which are of selling value, lack of knowledge in more attractive product packaging, and not having a well-structured financial bookkeeping system. The solutions offered are in the form of outreach about maximizing the use of tofu dregs that can be of marketable value, designing product labels, as well as training in making ice cream and tofu dregs sticks, product packaging techniques, and making simple financial reports. This activity is carried out in three stages, namely preparation, implementation and evaluation. The method used is the Participatory Rural Appreciation (PRA) method with lecture techniques, interactive discussions, demonstrations and direct practice. This activity went well. partners gained knowledge about making ice cream and sticks from solid tofu dregs, as well as increased partner motivation in developing their business, namely by selling ice cream products and tofu dregs stick